Case Report: Clinical Management of a Patient With Metastatic Non-Small Cell Lung Cancer Newly Receiving Immune Checkpoint Inhibition During Symptomatic COVID-19 - Mellinghoff, Sibylle C.; Vanshylla, Kanika; Dahlke, Christine; Addo, Marylyn M.; Cornely, Oliver A.; Klein, Florian; Persigehl, Thorsten; Rybniker, Jan; Gruell, Henning; Bröckelmann, Paul J. (Frontiers in Immunology, 2021)
Effects of initiation of programmed-death-protein 1 (PD1) blockade during active SARS-CoV-2 infection on antiviral immunity, COVID-19 course, and underlying malignancy are unclear. We report on the management of a male in his early 40s presenting with highly symptomatic metastatic lung cancer and active COVID-19 pneumonia. After treatment initiation with pembrolizumab, carboplatin, and pemetrexed, the respiratory situation initially worsened and high-dose corticosteroids were initiated due to suspected pneumonitis. After improvement and SARS-CoV-2 clearance, anti-cancer treatment was resumed without pembrolizumab. Immunological analyses with comparison to otherwise healthy SARS-CoV-2-infected ambulatory patients revealed a strong humoral immune response with higher levels of SARS-CoV-2-reactive IgG and neutralizing serum activity. Additionally, sustained increase of Tfh as well as activated CD4+ and CD8+ T cells was observed. Sequential CT scans showed regression of tumor lesions and marked improvement of the pulmonary situation, with no signs of pneumonitis after pembrolizumab re-challenge as maintenance. At the latest follow-up, the patient is ambulatory and in ongoing partial remission on pembrolizumab. In conclusion, anti-PD1 initiation during active COVID-19 pneumonia was feasible and cellular and humoral immune responses to SARS-CoV-2 appeared enhanced in our hospitalized patient. However, distinguishing COVID-19-associated changes from anti-PD1-associated immune-related pneumonitis posed a considerable clinical, radiographic, and immunologic challenge.